Motivasi usahawan wanita bumiputera di Sarawak:kajian ke atas perusahaan kecil dan sederhana - Noorhasmah binti, Yahya (Universiti Malaysia Sarawak (UNIMAS), 2006)
The study on bumiputera women entrepreneurs in Small and Medium Enterprises at Kuching, Sarawak has been undertaken with the main objective is to identify and investigate the factors that motivate bumiputera women entrepreneurs to involve in a business. The methodology used is questionnaire distribution with 50 respondents involved. The data was analyzed by using descriptive and inference statistic such as Chi-square test and Spearman Correlation. The study confirms, the first hypothesis which is bumiputera women entrepreneurs involved in the business is caused by push factors (family business motivation and financial motivation). On the other hand, the second hypothesis which is pull factors (social status motivation and lifestyle motivation) is found to be insignificant to the bumiputera women entrepreneurs’ involvement in the business. This study also found out that, bumiputera women entrepreneurs’ personalities such as self-achievement, future oriented and self-confident are very significant. Meanwhile, this study also identified the main problems face by bumiputera women entrepreneurs are the difficulty to get a loan, lack of capital and lack of skill in organizing and planning.